2021
DOI: 10.2147/cmar.s297094
|View full text |Cite
|
Sign up to set email alerts
|

A CT-Based Tumoral and Mini-Peritumoral Radiomics Approach: Differentiate Fat-Poor Angiomyolipoma from Clear Cell Renal Cell Carcinoma

Abstract: Objective This study aimed to evaluate the role of tumor and mini-peritumor in the context of CT-based radiomics analysis to differentiate fat-poor angiomyolipoma (fp-AML) from clear cell renal cell carcinoma (ccRCC). Methods A total of 58 fp-AMLs and 172 ccRCCs were enrolled. The volume of interest (VOI) was manually delineated in the standardized CT images and radiomics features were automatically calculated with software. After methods of feature selection, the CT-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…This approach overcame the problem related to the accurate delineation of tumoral volume of interest (VOI). 52 The same authors provided, in addition, a radiomics CT nomogram for discriminating AML from RCC, 53 built using selected features reaching an AUC, for this nomogram, of 0.968. 54 More recently, Han et al performed a retrospective research in 58 patients with AML and 140 with RCC, pathologically confirmed, to evaluate the prognostic value of CT radiomics in distinguishing AML from RCC.…”
Section: Resultsmentioning
confidence: 99%
“…This approach overcame the problem related to the accurate delineation of tumoral volume of interest (VOI). 52 The same authors provided, in addition, a radiomics CT nomogram for discriminating AML from RCC, 53 built using selected features reaching an AUC, for this nomogram, of 0.968. 54 More recently, Han et al performed a retrospective research in 58 patients with AML and 140 with RCC, pathologically confirmed, to evaluate the prognostic value of CT radiomics in distinguishing AML from RCC.…”
Section: Resultsmentioning
confidence: 99%
“…A majority of studies focused on the characterization of solid renal neoplasms (benign vs malignant) using MRI-based quantitative radiomics analyses (e.g., histogram and texture features) (34)(35)(36). However, only a small portion of studies aimed to distinguish subtypes of benign and malignant renal tumors, for instance, mf-AML and ccRCC (37)(38)(39)(40)(41). These studies proposed a CT-based radiomics model for preoperative differentiating mf-AML from homogeneous ccRCC (37)(38)(39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…However, only a small portion of studies aimed to distinguish subtypes of benign and malignant renal tumors, for instance, mf-AML and ccRCC (37)(38)(39)(40)(41). These studies proposed a CT-based radiomics model for preoperative differentiating mf-AML from homogeneous ccRCC (37)(38)(39)(40)(41). Ma et al observed that mini-peritumoral and perirenal radiomics features contributed to the differentiation of mf-AML from ccRCC (38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis of adherent perinephric fat concluded that it leads to an increased blood loss and a prolonged operating time (6). It has been reported that the radiomics model combining tumoral and peritumoral radiomics features was of most significance in distinguishing renal angiomyolipoma and ccRCC (7). Therefore, understanding its tumoral and peritumoral peculiarity such as perirenal fat thickness (8) has assumed great significance in clinical and pathological research, as well as in treatment decisions (2).…”
Section: Introductionmentioning
confidence: 99%